Análise de fator de necrose tumoral e deus receptores em soro e líquido intracístico em neoplasias de ovário - BORGES JÚNIOR, Luciano Eliziário (2017)
INTRODUCTION: Ovarian cancer is a major challenge for gynecological oncologists. Despite a vast amount of clinical and laboratory research, improvement in surgical techniques and an increasing array of chemotherapeutic agents, ovarian cancer still remains the most lethal gynecological malignancy and a leading cause of morbidity for the majority of those suffering with the disease. There is an important need for the development of new biomarkers for the diagnosis and prognosis of this neoplasia, which may also serve as targets for new therapeutic modalities. OBJECTIVES: The objectives of the study are to compare the dosage of TNF-α and its soluble receptors (sTNF-1R1 and sTNF-R2) in the serum and intracellular fluid between the group of benign neoplasms and that of primary ovarian malignancies and to relate the dosage of TNF-α, sTNF-1R1 and sTNF-R2 in serum and intracellular fluid of patients with malignant ovarian neoplasia with clinical and pathological prognostic factors. MATERIALS E METHODS: Sixty three patients were evaluated at the Pelvic Mass Ambulatory of the Federal University of the Triângulo Mineiro (UFTM) and submitted to surgery according to predetermined criteria, 17 malignant neoplasms and 46 benign neoplasms. Quantification of TNF-α and its soluble sTNF-R1 and sTNF-R2 receptors in serum and intracellular fluid was performed by the ELISA method. Serum collection was performed preoperatively. The data were analyzed statistically. The results were expressed in medians and percentiles. Results between the unpaired groups (benign and malignant neoplasms) were compared by Mann-Whitney test. The evaluation of prognostic factors was performed using the chi-square test, with significance level lower than 0.05. The differences were considered significant at p <0.05.RESULTS: Intracystic TNF-R2 levels were significantly higher in malignant neoplasms compared to benign neoplasms (p = 0.0235). There was no statistical significance in the comparisons of TNF and TNF-R1 in the intracellular fluid, nor in serum dosages. In the evaluation of prognostic factors, higher intracystic TNFR2 values were related to type II ovarian cancer with a tendency to significance (p = 0.0823). Higher intracystic TNFR2 values were related to degrees of differentiation 2 and 3 (p = 0.0087). Statistical evaluation was not statistically significant.